2011
DOI: 10.1139/w11-013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the bacterial community within carrot wash water

Abstract: Vegetables are washed after harvest to remove unwanted organic and inorganic particles, but wash water contaminated with certain pathogenic microorganisms can potentially contaminate produce. In this study, the microbial diversity of wash water was analyzed in samples taken from a carrot-processing facility. A 16S rRNA gene library with 427 clones was constructed and analyzed by amplified rDNA restriction analysis. For taxonomic classification, the 16S rRNA gene nucleotide sequences of 94 amplified rDNA restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
1
11
0
2
Order By: Relevance
“…Hausdorf et al . () found both P. agglomerans and R. aquatilis in wash water from an industrial carrot washing and packing plant. It is possible that these bacteria were merely secondary colonizers that flourished in the nutrient‐rich exudate generated by L. mesenteroides .…”
Section: Discussionmentioning
confidence: 99%
“…Hausdorf et al . () found both P. agglomerans and R. aquatilis in wash water from an industrial carrot washing and packing plant. It is possible that these bacteria were merely secondary colonizers that flourished in the nutrient‐rich exudate generated by L. mesenteroides .…”
Section: Discussionmentioning
confidence: 99%
“…is the fourth most prevalent bacteria in carrot wash water (Hausdorf et al . ). Also, 20% of fresh lettuce collected from retail markets in Valencia, Spain, was contaminated with A. butzleri (Gonzalez and Ferrus ).…”
Section: Introductionmentioning
confidence: 97%
“…Although A. butzleri contamination is documented mostly in meat products such as chicken and pork (Ho et al 2008;Lee et al 2010), it was recently reported that Arcobacter spp. is the fourth most prevalent bacteria in carrot wash water (Hausdorf et al 2011). Also, 20% of fresh lettuce collected from retail markets in Valencia, Spain, was contaminated with A. butzleri (Gonzalez and Ferrus 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Poultry intestines have been proposed to harbor Arcobacters and contaminate the slaughter houses during processing of the carcasses thereby enhancing the chances of further contamination (Ho et al 2008a). Arcobacters have also been recovered from a variety of foods of animal origin, namely beef, pork, milk, and sea foods, and also from water and vegetables (Son et al 2006;Collado et al 2010;Hausdorf et al 2011;Patyal et al 2011;Shah et al 2012a;Hausdorf et al 2013;Lee & Choi 2013;Rahimi et al 2014;Ramees et al 2014a;Lehmann et al 2015;Ferreira et al 2016). Contaminated water and meat play an important role in its transmission (Snelling et al 2006;Collado et al 2010;Gonz alez & Ferrus 2011;Rahimi 2014).…”
Section: Introductionmentioning
confidence: 99%